Image Based Object Tracking Target on Ship Robot for Oil Waste Cleaner - Richa Watiasih; Ahmadi; Adiananda (Fakultas Teknik Universitas Bhayangkara, 2022)
The existing oil waste water contains oil, solids, water and heavy metals. This oil waste is a contaminant material that can cause negative impacts to the aquatic environment as well as the existing living creatures around it so that it requires a careful and fast handling to clean. The research resulted in the tracking system on the image-based-ship robot by using the method of histogram and fuzzy logic controller that can detect the image of waste water well. The result of the testing of the ship robot done on the pool indicated that it took about ± 196.92 seconds for the robot to detect the image of oil waste objects. The oil waste suctioning process took a maximum of 60 seconds for once.